Território e produção de alimento: Estudos sobre as mediações das Comunidades Tradicionais aos quadros de fome e Insegurança alimentar no campo - PEREIRA, Ronald Bruno da Silva (2023)
This investigative study focused on analyzing the effects of territorial conflicts and social inequality on traditional groups, particularly quilombolas, specifically regarding food production, and how this scenario ends up triggering phenomena of food insecurity and hunger within these communities. It aimed to establish a better understanding of hunger as a social phenomenon in rural areas. Within this research, the quilombola territory of Charco, in São Vicente Ferrer, Maranhão, witnessed some points of understanding for this issue through reports and its historiography. These were collected with the assistance of field activities and interviews with local leaders. Furthermore, the study also explored the interconnection between access to secure territories, food production, and the vital role of territory and access to it for traditional communities in mitigating food scarcity. By examining their practices and territorial mediations, it was revealed how these groups face obstacles and offer solutions in the face of food shortages fueled by conflict situations, such as the Foro regime that affects these collectives. The critical importance of preserving and continuously accessing territories for food security in rural areas was highlighted.